AN ANALYSIS OF TRANSITIVITY OF WORDSWORTHâ€™S POEM â€I WANDERED LONELY AS A CLOUDâ€ - Natasya Ivana Bunmo (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2023)
According to the theory of Systemic-Functional Linguistics (SFL), language cannot bedisassociated from meaning. Function and semantics, as SFL suggests, are considered as thebasis of human language and communicative activity. In order to reveal the inseparability oflanguage and semantic, this study aims at analyzing transitivity in the poem entitled IWandered Lonely as a Cloud by William Wordsworth. This study occupies the qualitativedescriptive analysis method, in order to find out the type of process in transitivity. Afteranalyzing the data from the poem entitled I Wandered Lonely as a Cloud by WilliamWordsworth, this research finally is able to posit that there are four process types of six typesappearing; they are material process, mental process, behavioral process and relationalprocess. Due to identify which type of process more often appears in the poem, the researchersfinds that material process appeared more often than others; after that, mental process,behavioral process and relational process.